دراسة فعالية وجودة الصوت في خوارزميات ضغط الصوت - فاروسي فاتن (Latakia University Journal -Engineering Sciences Series, 2017)
يعد الصوت عنصراً أساسياً من عناصر الأوساط المتعددة، ونتيجة الحاجة إلى استخدامه في كثير من التطبيقات الحياتية كالبث التلفزيوني وبرامج التواصل، لذا كانت الضرورة لوجود تقنيات لمعالجة إشارة الصوت من ضغط وتحسين وتقليل ضجيج تكمن أهمية عملية ضغط البيانات في تخفيض معدل البتات المستخدمة، وذلك عن طريق ترميز المعلومات باستخدام عدد أقل من البتات من التمثيل الأصلي من أجل الإرسال والتخزين. حيث تقوم بتحديد المعلومات غير الضرورية وإزالتها،أي تعطي المعلومات التي ضُغطت ضغط الاستخدام ما نحتاجه كشكل أساسي وليس أدق التفاصيل. يهدف البحث إلى دراسة كيفية معالجة الصوت والإشارة الموسيقية، وهي عملية تضم بعض التطبيقات كالترميز والضغط الرقمي بهدف النقل الفعال والتخزين على الهواتف النقالة ومشغلات الموسيقا المحمولة، ونمذجة واستنساخ صوت الآلات الموسيقية وقاعات الموسيقا وتوافقيات الموسيقا الرقمية، وتحرير الموسيقا الرقمية، وتصنيف محتوى الموسيقا بالإضافة إلى أمور أخرى. The sound is an essential component of multimedia, and due to the needto be used in many life applications such as television broadcasting andcommunication programs, so it was necessary for the existence of audio signal processing techniquessuch as compressing, improving, and noisereduction. Data compression process aims to reduce the bit rate used, by doing encoding information using fewer bits than the original representation for transmitting and storing. By this process,the unnecessary information is determined and removed, that means it gives the compressed information for useable compression, which we need as a fundamental, not the minutest details. This research aims to study how to process sound and musical signal. It’s a process that consists of a wide range of applications like coding and digital compression for the effective transport and storage on mobile phones and portable music players, modeling and reproduction of the sound of musical instruments and music halls and the harmonics of digital music, editing digital music, and classification of music content, and other things.